2006
DOI: 10.1051/0004-6361:20064809
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of solar UV irradiance in cycle 23

Abstract: Solar irradiance variations show a strong wavelength dependence. Whereas the total solar irradiance varies by about 0.1% during the course of the solar cycle, variations at the wavelengths around the Ly-α emission line near 121.6 nm range up to 50−100%. These variations may have a significant impact on the Earth's climate system. Being almost completely absorbed in the upper atmosphere, solar UV radiation below 300 nm affects stratospheric chemistry and controls production and destruction of ozone. Models of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
155
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 112 publications
(170 citation statements)
references
References 55 publications
(79 reference statements)
12
155
2
1
Order By: Relevance
“…It is not yet clear to what extent this unexpectedly large change reflects different instrumentation or how much it may be due to the long-term trends that have combined with the solar cycle to generate the current unusual solar minimum. The SATIRE modelling of the variability of the spectrum, extended into the UV by Krivova et al (2006), shows some similarities and some difference to the SIM results on both solar cycle and solar rotation time scales (Unruh et al 2008), but does not give as large a change in the UV as reported from SIM data.…”
Section: Spectral Irradiance Changes and Se Effectsmentioning
confidence: 73%
“…It is not yet clear to what extent this unexpectedly large change reflects different instrumentation or how much it may be due to the long-term trends that have combined with the solar cycle to generate the current unusual solar minimum. The SATIRE modelling of the variability of the spectrum, extended into the UV by Krivova et al (2006), shows some similarities and some difference to the SIM results on both solar cycle and solar rotation time scales (Unruh et al 2008), but does not give as large a change in the UV as reported from SIM data.…”
Section: Spectral Irradiance Changes and Se Effectsmentioning
confidence: 73%
“…2, also including the UV. We construe this as an independent support to both the Krivova et al (2006) method and the reliability of the "SATIRE-NESSY" time series.…”
Section: Spectral Irradiance Variability On Different Timescalesmentioning
confidence: 86%
“…The error bars establish that the disagreement between SIM and SATIRE-S exceeds the estimated long-term uncertainty of the instrument. It should be noted that given that the decline in TSI over this period is approximately a third of the maximum-to-minimum variation, this sets the cycle variation a significant factor above that observed by UARS/SUSIM and UARS/SOLSTICE (Floyd et al 2003;Krivova et al 2006). Over a similar period in the previous cycle, August 1993 to May 1996 (solar minimum), the 200−300 nm region declined by 0.06 W m −2 from 14.51 to 14.45 W m −2 according to level 3BS V22 SUSIM data on UARS.…”
Section: Uv 201-300 Nmmentioning
confidence: 93%
“…In the past it was assumed that the radiative forcing on Earth was directly proportional to this change in the total solar output, and although there is evidence that changes in TSI do affect the climate (Labitzke & van Loon 1995;van Loon & Shea 1999), it is becoming clear that spectral solar irradiance (SSI) is also an important factor when considering the Sun's impact on climate (Haigh 1994). It has previously been estimated that 60% of TSI variability is found in ultra-violet (UV) wavelengths below 400 nm (Krivova et al 2006). The UV domain is known to affect stratospheric temperatures and chemistry; most notable and well-established is its effect on ozone (Labitzke et al 2002;Haigh 2007).…”
Section: Introductionmentioning
confidence: 99%